A participação de amigos em casos de violência contra a mulher por parceiro íntimo nos contextos online e offline. - Pedruzzi, Pamela Fardin (2020)
Intimate Partner Violence (abbreviated as IPV) is a worldwide attention-grabbing phenomenon. In Brazil, and especially in the state of Espírito Santo, the numbers of affected women grow each year. From this perspective, the present research aimed to analy